An Exploratory Use of Web Content Analysis to Understand Cruise Tourism Services. (5th September 2012) - Brejla, Paul; Gilbert, David
ABSTRACT Research within the cruise industry now has the ability to utilize Web‐based content analysis. This paper provides an example of a methodology that explores patterns of co‐creation of value on board cruise ships using holiday reviews retrieved through Web content mining from CruiseCritic.com. The aim is to add to the field of co‐creation and cruise tourism by providing an approach to exploratory Web‐based data collection. With the use of a data‐driven approach to knowledge discovery, this paper provides a means to achieve a deeper understanding of guest‐to‐guest and guest‐to‐staff interactions on board cruise ships. Copyright © 2012 John Wiley & Sons, Ltd.